Annual and Diurnal Trend of Surface Ozone (O3) in Industrial Area - Mohd Napi N.N.L.; Abdullah S.; Ahmed A.N.; Mansor A.A.; Ismail M. (Institute of Physics Publishing, 2023)
Air pollution; Developing countries; Ozone; Population statistics; Sustainable development; Adverse effect; Atmospheric pollution; Average concentration; Concentration values; Industrial area; Population growth; Short-term effects; Surface ozone; Analysis of variance (ANOVA)